2012
DOI: 10.1186/1471-2229-12-15
|View full text |Cite
|
Sign up to set email alerts
|

The role of the Arabidopsis FUSCA3transcription factor during inhibition of seed germination at high temperature

Abstract: BackgroundImbibed seeds integrate environmental and endogenous signals to break dormancy and initiate growth under optimal conditions. Seed maturation plays an important role in determining the survival of germinating seeds, for example one of the roles of dormancy is to stagger germination to prevent mass growth under suboptimal conditions. The B3-domain transcription factor FUSCA3 (FUS3) is a master regulator of seed development and an important node in hormonal interaction networks in Arabidopsis thaliana. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
94
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(101 citation statements)
references
References 67 publications
(134 reference statements)
7
94
0
Order By: Relevance
“…Yamamoto et al (2010) documented transcriptomes in developing seed of fus3 compared with the wild type and assessed transcript accumulation in response to an inducible form of FUS3. Chiu et al (2012) examined transcript accumulation in response to supraoptimal imbibition temperatures in wild-type seeds, an environment where FUS3 has been found to have a protective function. Lumba et al (2012) examined the consequences of inducible FUS3 in seedlings where FUS3 has been shown to have roles in vegetative phase transitions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Yamamoto et al (2010) documented transcriptomes in developing seed of fus3 compared with the wild type and assessed transcript accumulation in response to an inducible form of FUS3. Chiu et al (2012) examined transcript accumulation in response to supraoptimal imbibition temperatures in wild-type seeds, an environment where FUS3 has been found to have a protective function. Lumba et al (2012) examined the consequences of inducible FUS3 in seedlings where FUS3 has been shown to have roles in vegetative phase transitions.…”
mentioning
confidence: 99%
“…Here, we report the genome-wide identification of in vivo binding sites for FUS3 in an embryonic culture tissue system that allows robust ChIP. The data sets generated by Yamamoto et al (2010), Chiu et al (2012), and Lumba et al (2012) were used to identify FUS3-responsive genes. Yamamoto et al (2010) documented transcriptomes in developing seed of fus3 compared with the wild type and assessed transcript accumulation in response to an inducible form of FUS3.…”
mentioning
confidence: 99%
“…11,12,13 Overexpression of FUS3 at 32 C completely inhibit germination through de novo ABA synthesis, this allows higher seedling survival when seeds are transferred to optimal temperature. 13 To elucidate the mechanism behind FUS3 protein accumulation under heat stress, we recently characterized FUS3 degradation rates in extracts of seed imbibed at optimal temperature (21 C) in the presence of ABA and at supra-optimal (32 C) temperatures. 14 By using ABA biosynthetic mutants and fluridone, an inhibitor of ABA biosynthesis, we showed that FUS3 degradation in vitro CONTACT Sonia Gazzarrini gazzarrini@utsc.utoronto.ca Addendum to: Chiu RS, Pan S, Zhao R, Gazzarrini S. ABA-dependent inhibition of the ubiquitin proteasome system during germination at high temperature in Arabidopsis.…”
Section: Introductionmentioning
confidence: 99%
“…5,10 At elevated temperatures, ABA levels increase and this leads to a delay or inhibition of germination (thermoinhibition) and FUS3 accumulation. 11,12,13 Overexpression of FUS3 at 32 C completely inhibit germination through de novo ABA synthesis, this allows higher seedling survival when seeds are transferred to optimal temperature. 13 To elucidate the mechanism behind FUS3 protein accumulation under heat stress, we recently characterized FUS3 degradation rates in extracts of seed imbibed at optimal temperature (21 C) in the presence of ABA and at supra-optimal (32 C) temperatures.…”
mentioning
confidence: 99%
See 1 more Smart Citation